Rough Guides phrasebook Mandarin (Rough Guide phrasebook, 2019)
Compact, clear, and packed with key words and phrases to help conversation, this pocket-sized Mandarin phrasebook and dictionary from Rough Guides' trusted language experts (with free app) is a trusty travel companion, and all you need to make yourself understood - and to understand others - when you're out and about in China and other Mandarin-speaking countries. With its emphasis on conversational usage, and up-to-date language on social media, leisure, business - and more - this is the only phrasebook you'll need when exploring China and other Mandarin-speaking countries; Includes 7000-word bilingual dictionary; Visually appealing colour-coding system means you can find what you want, when you want, and fast; Rough Guides' simplified pronunciation system will ensure you're clearly understood; Stunning colour photography enhances the expert content, and makes this series the most visually attractive phrasebook on the market.